A JURIDICAL ANALYSIS OF HOSPITAL REFUSAL OF BADUY INDIGENOUS PATIENTS FOR THE ABSENCE OF A NATIONAL IDENTIFICATION NUMBER (NIK) (INTERNATIONAL SEMINAR, 2025)
patient by a hospital on the grounds of lacking a National Identification Number (NIK), examined within the framework of Indonesia’s prevailing legal regulations. This phenomenon reflects a tension between administrative obligations within the public service system and the universal human right to health. The research employs a normative legal method, utilizing both the statute approach and the conceptual approach. The data sources consist of primary, secondary, and tertiary legal materials, which are analyzed qualitatively through interpretation and synchronization of relevant legal norms. The findings indicate that the hospital’s refusal to treat a patient without an NIK contradicts the provisions of Law No. 17 of 2023 on Health, Law No. 39 of 1999 on Human Rights, and the principle of recognition of customary law communities as stipulated in Law No. 6 of 2014 on Villages. Although Law No. 24 of 2013 on Civil Registration requires the possession of an NIK as an official identity, such a requirement cannot be used to justify the denial of access to constitutionally guaranteed health services. This study underscores the necessity of legal harmonization and the implementation of affirmative policies to ensure the rights of indigenous communities to non-discriminatory access to health services.